2017
DOI: 10.1016/j.cattod.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Studying two-dimensional zeolites with the tools of surface science: MFI nanosheets on Au(111)

Abstract: While surface science has provided fundamental insights into a variety a materials, the most used catalysts in the industry, namely zeolites, still remain a challenge. The recent preparation of two-dimensional versions of MFI zeolite frameworks and the possibility of their deposition on electrically conductive supports provides for the first time a viable strategy to perform detailed studies on industrially relevant zeolites using the vast toolkit of surface science. In this work we demonstrate the use of infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A photon energy of 750 eV was used in our studies, which was calibrated and referenced to the Fermi level of the Ru(0001) substrates. Infrared reflection absorption spectroscopy (IRRAS) experiments were carried out in a home-built UHV system equipped with a Bruker Vertex 70 spectrometer [17]. This system is also capable of polarization modulation (PM) IRRAS experiments at pressures up to 1 Atm.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…A photon energy of 750 eV was used in our studies, which was calibrated and referenced to the Fermi level of the Ru(0001) substrates. Infrared reflection absorption spectroscopy (IRRAS) experiments were carried out in a home-built UHV system equipped with a Bruker Vertex 70 spectrometer [17]. This system is also capable of polarization modulation (PM) IRRAS experiments at pressures up to 1 Atm.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…24 In the MFI nanosheets supported on Au(111), we observed a high frequency (HF) mode of 1247 cm −1 and a low frequency (LF) mode of 1174 cm −1 (Figure 1a), which are consistent with the measurements shown in a previous report. 25 Kestell et al previously suggested that the HF mode likely corresponds to Si−O−Si linkages between the pores, while the LF mode corresponds to internal linkages within the pores. 25 The peak position at 3724 cm −1 (Figure 1c) corresponds to SiOH groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The nanosheet-seeded MFI nanosheets were coated on an Au(111) crystal and placed in a high-vacuum chamber with BaF 2 windows that allow the passage of IR light to study phonon vibrations of materials and vibrational modes of adsorbed molecules, under a wide range of pressures and temperatures. Under high vacuum (~2 × 10 −4 Pa) and ambient temperature, three phonon modes at 1095, 1176, and 1248 cm −1 are obtained, corresponding to MFI framework vibrations ( 39 ). Exposure to xylene vapor yields additional vibrational modes, which arise from the aromatic ring vibrations of adsorbed xylene molecules.…”
Section: Resultsmentioning
confidence: 99%